Comparison of Performance of Fast‐Reacting Nanothermites and Primary Explosives. Issue 7 (28th February 2017) - Khasainov, Boris; Comet, Marc; Veyssiere, Bernard; Spitzer, Denis
Abstract: The main features of nano‐sized thermites are reviewed with the purpose to compare the performance of most reactive nanothermites showing high combustion front velocities of up to 2500 m s −1 with that of primary explosives. Because these regimes do propagate only at very low relative density of nano‐thermites and as convective burning waves rather than detonations, the initiating capacity of these nanocompositions, compared to promises, is yet much lower than that of the primary explosives. Hybrid mixtures of nanothermite with high explosive offer practically interesting triggering potential and present a more promising way for substituting lead‐based "not green" primary explosives. A threshold size of nanothermite particles is evaluated above which the dynamics of flame propagation in nanothermites can be reasonably described based on the principles of continuum mechanics and classical thermodynamics. Abstract :